NATURAL PHOSPHATE-SULFATE MELTS - Naumov V.B.; Solovova I.P.; Kovalenko V.I.; Turkov V.A.; Malov V.S.; Samoylov V.S. (My University, 1988)
A study of the numerous primary microinclusions found in apatite crystals from the Mushugay-Khuduk carbonatite complex (Mongolia) established the presence of natural phosphate-sulfate melts and their basic characteristics. The crystals studied came from the Apatitovyy rare earth and apatite ore body with a stock-like form measuring approx. 30 × 70 m and traced down to 200 m in boreholes. It cuts across its host syenite-porphyry massif, and numerous schlieren-like segregations of apatite ore, as also veins of it are observed in the exocontacts of the syenite-porphyry. Additional aspects of the subject are discussed.